2017
DOI: 10.17987/icfj.v11i0.414
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Risk Factor Burden in the United Arab Emirates (UAE): The Africa Middle East (AfME) Cardiovascular Epidemiological (ACE) Study Sub-analysis

Abstract: Highlights BackgroundThe Africa Middle East (AfME) Cardiovascular Epidemiological (ACE) study demonstrated that cardiovascular risk factors are highly prevalent among relatively young adult outpatients attending general practice clinics across AfME regions. ObjectiveBased on broader AfME estimates from the ACE Study, this sub-analysis evaluated the prevalence of cardiovascular risk factors in the United Arab Emirates (UAE), particularly in rural and urban cohorts attending general practice clinics. MethodsData… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 33 publications
(46 reference statements)
2
5
0
Order By: Relevance
“…Less than one third of our study population have dyslipidaemia. However, our finding was counterpart with data from ACE (Cardiovascular Epidemiological) study in United Arab Emirates, the prevalence was 74% [39], while the high prevalence of dyslipidaemia in our study in young adults (age 25-34years) calls for an earlier screening for dyslipidaemia and other risk factors. Another important factor observed in our study was the proportion of people with low physical activity, it was estimated that half of the population 48.3% had low physical activity.…”
Section: Discussionsupporting
confidence: 87%
“…Less than one third of our study population have dyslipidaemia. However, our finding was counterpart with data from ACE (Cardiovascular Epidemiological) study in United Arab Emirates, the prevalence was 74% [39], while the high prevalence of dyslipidaemia in our study in young adults (age 25-34years) calls for an earlier screening for dyslipidaemia and other risk factors. Another important factor observed in our study was the proportion of people with low physical activity, it was estimated that half of the population 48.3% had low physical activity.…”
Section: Discussionsupporting
confidence: 87%
“…The changing prevalence of hypertension in the UAE is mainly due to changing lifestyles with lower physical activity and a shift from a traditional diet that is high in fiber to energy-dense processed food high in fat, sugar, and salt [ 32 , 33 , 34 ]. Furthermore, studies consistently reported a significantly increased burden of overweight and obesity [ 35 ], metabolic syndrome [ 36 ], and cardiovascular risk factors [ 37 ] among the younger population in recent decades. Therefore, public health authorities should initiate multifaceted interventions to control the pervasive burden of hypertension in the UAE.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies have shown that MetS is strongly associated with accelerated atherosclerosis, which considerably increases the rates of atherosclerotic events, including myocardial infarction and stroke, and increases the risk of cardiovascular mortality ( 4 – 6 ). In the United Arab Emirates (UAE), myocardial infarction and strokes represent the first- and third-most common causes of premature death, respectively, and combined, they caused ~40% of all deaths in 2017 ( 7 , 8 ). Recently, increasing rates of all five components of MetS have been reported in the UAE.…”
Section: Introductionmentioning
confidence: 99%